Poor or no poor? Pragmatic and idealistic perspectives on the poor in Deuteronomy 15:1-11 - Bosman, HL (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
In this article I would like to discuss Deuteronomy 15:1-11 as an example of how the Old Testament engages with the challenge of poverty in a pragmatic and idealistic way. My hypothesis boils down to presuming that the provisions related to the poor in Deuteronomy 15:1-11 are linked to the third commandment concerning the keeping of the Sabbath. This hypothesis, I would like to argue, has significant implications for our theological-ethical reflection on why believing communities should address the problem of poverty in Africa.